Endemic occurrence of Fasciola hepatica in an alpine ecosystem, Pyrenees, Northeastern Spain. Issue 4 (14th October 2020) - Roldán, Claudia; Begovoeva, Mattia; López‐Olvera, Jorge Ramón; Velarde, Roser; Cabezón, Óscar; Molinar Min, Anna Rita; Pizzato, Federica; Pasquetti, Mario; Fernández Aguilar, Xavier; Mentaberre, Gregorio; Serrano, Emmanuel; Puig Ribas, Maria; et al.
Abstract: Fasciola hepatica is a liver parasite of ruminants whose distribution is determined by its intermediate host, the freshwater snail Galba truncatula . In Europe, F. hepatica is mostly associated with lowlands. Infection from sympatric domestic reservoirs is rarely reported in wild mountain ungulates. This study explores F. hepatica in a multi‐host system in a European alpine area. Serum samples ( n  = 1, 209) from Pyrenean chamois ( Rupicapra p. pyrenaica ), European mouflon ( Ovis aries musimon ), domestic sheep ( Ovis aries ) and domestic cattle ( Bos taurus ) were collected in the National Game Reserve of Freser‐Setcases (NGRFS) in Catalonia, Northeastern Spain, from 2008 to 2019, and tested for antibodies against F. hepatica . During the same period, the livers of 214 chamois hunted in the NGRFS were inspected for F. hepatica and associated pathological changes. Finally, 907 freshwater snails were collected in summer 2016 between 1559 and 2, 224 metres above sea level (asl) in the NGRFS, and F. hepatica DNA sought by PCR. Antibodies against F. hepatica were detected in all four species, with a higher prevalence in cattle and sheep than in chamois. Fasciola hepatica and hepatic lesions were concurrently observed in 13/214 of the chamois livers inspected (6.1%, CI95 2.9%–9.3%). Fasciola hepatica DNA was detected in one out of the 907 snails (0.1%, Cl95 0.1% – 0.3%; Ct value 33.3) and collected at 2054 m asl. Fasciola hepatica was consistently detected in a high mountain multi‐host system, suggesting that its life cycle is completed and that it occurs endemically at the highest elevation reported in Europe. Transhumant livestock are the likely source in this alpine ecosystem, which according to rare occurrence of F. hepatica DNA in G. truncatula is still a suboptimal habitat for F. hepatica life cycle. Studying parasites at their highest distribution range can be useful to monitor climate change in seasonal mountain environments.